Odra River in Lower Silesia: probabilistic analysis of flood risk dynamics as part of sustainable development of water management - Kuzminski, Lukasz; Halama, Arkadiusz (Managerial Economics, 2019)
One of most common natural catastrophes in Poland are undoubtedly floods. Climatic change contributes to more and more often and violent occurrences of the maximum flow in rivers, which increases flood damage. Inadequate land management and the unjustified belief in the effectiveness of technical flood control measures can also contribute to flood damage. The development of water management (including flood protection) should be carried out in a sustainable way by integrating social, environmental, and economic objectives. In flood protection, those measures that are least invasive to the natural environment should be used first; in particular, non-technical flood protection methods (e.g., flood risk assessment and management, and the proper definition and management of flood plains). One of the bases for the sustainable development of water management is the preparation of models that can help us calculate the likelihood of maximum flow and to identify areas that are at risk of flooding. On this basis, the proper spatial policy and prevention of flood effects will be possible. This article presents the probabilistic analysis carried out on the flood risk dynamics for a selected area of the Odra River basin. The authors based their risk dynamic assessment on the results from the distributions of the maximum values for a selected hydrological characteristic – the flow rate. Based on the daily flow data from the years of 1994–2013 collected at a hydrological station on the Odra River in Malczyce, the 30-day flow maxima were set individually for four 5-year periods. Then, a probabilistic model of the maximum flow was developed based on these peaks for each 5-year period. The resulting models were used to estimate flood risks and for analyzing the dynamics for the studied area.